"Waiting for baby" : first-time parents talk about worries during pregnancy : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology, Massey University, Wellington, Aotearoa/New Zealand - Marshall, Annabel Florence (Massey University, 2013)
Previous research indicates that positive and negative changes of mood are not unusual during pregnancy, and both men and women may be faced with an overwhelming amount of worries [sic]. Although attention has begun to focus on the impact of anxiety disorders during pregnancy, less is known about the nature of the unique time-bounded concerns parents experience during this time. The purpose of this exploratory study was to increase understanding of expectant parents’ worries during first pregnancies. The research was guided by a social constructionist approach. By conducting semi-structured interviews, the study aimed to explore the ways a group of 20 first-time parents talked about worries during pregnancy, to bring us closer to the psychology of this transition. Participants were recruited through local antenatal education providers and by word of mouth. Interviews were audio-recorded digitally, transcribed by the researcher, and analysed discursively. Analysis focused on the discursive detail of worries, including how participants constructed worry, what they worried about, and how they managed and made sense of their concerns. The participants drew upon salient discourses to construct aspects of pregnancy and parenthood in a variety of ways. Similarities as well as differences emerged from the men’s and women’s data. An example of a marked difference was apparent in the way participants constructed worry. That is, while women drew upon a discourse of all-consuming worry to construct concerns as negative, pervasive and consuming, the men drew upon a discourse of sudden reality to construct their concerns as intense but comparatively short-lived, in response to a tangible event during pregnancy. Both women and men drew upon discourses of the healthy baby and responsibility to describe and explain the content of their worries. More positive aspects of their talk were captured by discourses of trust and positive change, which participants utilised to manage and make meaning of their concerns. Increased understanding of pregnancy-related worries is important for informing the development of psycho-education for new parents as well as therapeutic practices. Ultimately, helping new parents manage their worries is essential in preventing the development of more serious distress or illness, as well as working to strengthen the family unit.
Keywords: First time parents; Worry; Pregnancy fears; Expectant parents